Plädoyer für eine linguistische Partizipation an einem konstruktivistisch begründeten, kulturwissenschaftlichen Projekt transdisziplinärer Forschung am Beispiel der Interkulturellen Kommunikation - Hornscheidt, Antje (Linguistik Online, 2003)
In my article I take a constructivist perspective as a starting point. Giving some introductory remarks on the role of language and the constitution of meaning within a constructivist framework, the article discusses the role and relevance of Critical Discourse Analysis and Cognitive Linguistics within this frame for cultural studies. It is argued that a transdisciplinary approach is most valuable for a research taking the importance of linguistic processes for cultural analysis into account. Following especially Fauconnier (1999) and Verschueren (1999), the importance of a pragmatic and cognitive-linguistic approach to language is underlined. To exemplify the consequences that a transdisciplinary approach could have, the article focuses on the way intercultural communication has been conceptualized within linguistics so far. The critical analysis of traditional research on and conceptualization of intercultural communication shows, how a constructivist perspective can widen the scope of linguistic research.